DOI: 10.29007/pp26
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Industry Estimating Software Utilization Practices to Improve Construction Education

Abstract: Estimating is an essential part of any construction firm and a core subject in construction management education. Construction faculty should make every effort to align their courses with the needs of industry. A survey was completed by members of the American Society of Professional Estimators and the McWhorter School of Building Science Industry Advisory Council to determine what software was most prevalently utilized in industry for material quantification and cost estimating. A total of 186 practitioners r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The authors first conducted thorough research to identify estimating and project cost management platforms on the current market (Collins and Redden, 2022). The authors then established inquiries regarding the various identified platforms and the management protocols for data derived from those various identified platforms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors first conducted thorough research to identify estimating and project cost management platforms on the current market (Collins and Redden, 2022). The authors then established inquiries regarding the various identified platforms and the management protocols for data derived from those various identified platforms.…”
Section: Methodsmentioning
confidence: 99%
“…A couple of questions in the survey investigated the process of data transfer from estimating to the project cost control in project management systems which is traditionally known as an operations function in the United States. As stated previously, the literature identified Microsoft Excel and Sage Estimating as the most widely utilized software for creating, managing and/or finalizing project estimates (Collins & Redden, 2022;JB Knowledge, 2020). This study investigated the software used for project cost management after the project award.…”
Section: The Process Of Transferring Data From Estimating To Operationsmentioning
confidence: 99%
See 1 more Smart Citation